2022
DOI: 10.3390/ijerph191610131
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perception of Patient Safety Culture in a Referral Hospital: A Cross-Sectional Study

Abstract: Healthcare systems are becoming increasingly complex which is helping to promote a ‘culture of safety’ within them based on the best scientific evidence available. Indeed, creating a positive institutional culture of patient safety is reflected in health outcomes. The aim of this present study was to describe the perception of culture of safety by nurses in adult inpatient units in a tertiary hospital and to analyze adverse events reporting. It was a cross-sectional study in which 202 nurses from adult hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
2
1
0
1
Order By: Relevance
“…This means that their perception of reporting incidents affects the reporting process itself, as they see that reporting incidents expose them to the issue and is done as we mentioned in our discussion in the previous paragraphs that this was recorded as a negative point in their records, in addition to their fear of punishment. Our findings were supported by the study of Sosa-Palanca et al, Skutezky et al,and Burlison et al [26,30,34]. Generally, when healthcare providers do not have the courage and awareness of the importance of reporting incidents in terms of enhancing patient safety, this leads to a weakness in the incident reporting system in hospitals, as well as an increase in punitive that prevent the process of reporting incidents, and thus endangers patient safety.…”
Section: The Relationship Between Demographic Characteristics Of Heal...supporting
confidence: 84%
See 1 more Smart Citation
“…This means that their perception of reporting incidents affects the reporting process itself, as they see that reporting incidents expose them to the issue and is done as we mentioned in our discussion in the previous paragraphs that this was recorded as a negative point in their records, in addition to their fear of punishment. Our findings were supported by the study of Sosa-Palanca et al, Skutezky et al,and Burlison et al [26,30,34]. Generally, when healthcare providers do not have the courage and awareness of the importance of reporting incidents in terms of enhancing patient safety, this leads to a weakness in the incident reporting system in hospitals, as well as an increase in punitive that prevent the process of reporting incidents, and thus endangers patient safety.…”
Section: The Relationship Between Demographic Characteristics Of Heal...supporting
confidence: 84%
“…This may explain because the majority of the participants in the current study had more than five years of experience. This result is supported by the study conducted by Sosa-Palanca et al as it was concluded that nurses with more years of experience have a better perception of reporting incidents and errors, and they fear exposure to the issue if something goes wrong, and therefore fewer reporting incidents related to patient safety [30].…”
Section: The Relationship Between Demographic Characteristics Of Heal...supporting
confidence: 58%
“…Birinci bölümde katılımcılara ait tanıtıcı özellikleri belirlemeye yönelik (yaş, cinsiyet, eğitim durumu, çalıştığı birim, toplam çalışma süresi, hasta güvenliği konusunda hizmet içi eğitim alıp almadığı) dokuz soru bulunmaktadır. İkinci bölümde yer alan sorular ise literatürde daha önce yapılan çalışmalar [15][16] incelenerek hazırlanmıştır. Hazırlanan açık uçlu sorular katılımcıların hasta güvenliği ve hasta güvenliği kültürü hakkında bildiklerinin, hasta güvenliği ihlalinde en çok karşılaştıkları olayların, hasta güvenliğini ihlal eden faktörlerin ve hasta güvenliğinin sağlanmasında hem bireysel hem de kurumsal olarak yapılması gerekenlerin belirlenmesine yöneliktir.…”
Section: Veri Toplama Araçlarıunclassified
“…Studies conducted by Spanish and German researchers state that nurses often do not report adverse events that occur in the hospital [11,12]. The most important barriers are lack of support from managers and other staff, fear of consequences and punishment, too much work, education, professional duties, doubts about whether it is necessary and what needs to be reported, being afraid to appear as an incompetent specialist, seeing no point in reporting, and many more [11][12][13][14][15]. These findings suggest that nursing team members should be more knowledgeable about adverse events.…”
Section: Introductionmentioning
confidence: 99%